2017
DOI: 10.1002/cam4.1171
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma in children and adolescents: a systematic review of contemporary phase I and II clinical trials and biology update

Abstract: Survival rates for patients with medulloblastoma have improved in the last decades but for those who relapse outcome is dismal and new approaches are needed. Emerging drugs have been tested in the last two decades within the context of phase I/II trials. In parallel, advances in genetic profiling have permitted to identify key molecular alterations for which new strategies are being developed. We performed a systematic review focused on the design and outcome of early‐phase trials evaluating new agents in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 109 publications
(204 reference statements)
3
32
0
Order By: Relevance
“…Overall, temozolomide continues to be used in medulloblastoma treatment protocols as reviewed by Bautista et al and demonstrated by trials with various temozolomide combinations in salvage protocols and the addition of the agent in front‐line regimens (NCT00936156). The temozolomide‐topotecan combination results in similar activity to other combinations in children with heavily pretreated medulloblastoma with a favorable toxicity profile and will therefore likely be utilized further in front‐line or other salvage therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, temozolomide continues to be used in medulloblastoma treatment protocols as reviewed by Bautista et al and demonstrated by trials with various temozolomide combinations in salvage protocols and the addition of the agent in front‐line regimens (NCT00936156). The temozolomide‐topotecan combination results in similar activity to other combinations in children with heavily pretreated medulloblastoma with a favorable toxicity profile and will therefore likely be utilized further in front‐line or other salvage therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the extensive list of studies linking PC, Hh signaling, and tumorigenesis, it is not surprising that this pathway became an interesting cancer drug target. Smo inhibitors are FDA‐approved for treatment of advanced BCC and tested in clinical trials in medulloblastoma patients . The success of those therapeutics was, however, limited due to the development of drug resistance.…”
Section: General Considerations and Remarksmentioning
confidence: 99%
“…Reviewers will develop a comprehensive data extraction form on Microsoft Excel, as guided by Covidence's piloting forms, and data collection forms for RCTs by Cochrane Training, in addition to several peer-reviewed systematic reviews and protocols [36][37][38][39][40][41]. An initial calibration test will be conducted (AAA, SKS) on a set of 5 randomly selected articles and 5 randomly selected clinical trials to ensure high inter-rater agreement; the latter will compare manual and automatic data extraction methods (using Extracting Accurate efficacy and safety information from ClinicalTrials.gov, EXACT) [42].…”
Section: Selection and Data Collection Processmentioning
confidence: 99%